Analisis Kebijakan Pekerja Penyandang Disabilitas Menurut UU No. 8 Tahun 2016 pada Sektor BUMN - Bella Alizah; Desy Ilmiawati; Anggita Trisnawati; Mawar Mawar (Journal on Education, 2023)
People with disabilities are entitled to respectable work. Law Number 8 of 2016 concerning Persons with Disabilities was released by the Government of the Republic of Indonesia (UUPD). State-Owned Enterprises (BUMN) are required under Article 53 paragraph (1) UUPD to employ persons with disabilities at least 2% of all workers. In order to fulfill the right of persons with disabilities to get a job, this research was conducted to examine the possibilities and problems faced by stakeholders and persons with disabilities in BUMN. This study uses a qualitative descriptive research design. Fulfillment of these rights in BUMN has not been implemented, according to research findings. This occurs as a result of prejudice in certain industries and positions, a breakdown in acceptance and competency standards in the workplace, and the lack of education and skills of persons with disabilities.